EFFECTS OF PILATES METHOD IN THE TREATMENT OF CHRONIC LOW BACK PAIN: AN INTEGRATIVE REVIEW (Fiep Bulletin - online, 2014)
The low back pain is a symptom of multifactorial etiology that affects both genders and has high incidence in economically active population, temporarily or permanently disabling for execution of daily and professional activities. Due to the multiple etiologies, is a condition difficult to prevent and treat, finding the Pilates method a resource of great value and has shown great effectiveness in treating these pains. Thus, we sought to identify, through an integrative literature review, the contributions of studies related to the benefits of Pilates in chronic low back pain. The search was conducted in the following electronic databases: PubMed and Regional Library of Medicine (BIREME). We used the following descriptors: low back pain, and Pilates. These terms are indexed in the words of the Health Sciences (MeSH). We conducted a historical court including studies published in the last five years (2008 to 2013), where they found 472 articles, but only 8 met the pre-established criteria. It was found that in most studies there was significant improvement in decreasing pain and only 3 studies show that improvement occurred in the same way secondary to lumbar stabilization, demonstrating the need for more studies about the theme. According to this revision Pilates showed positive results in lumbopelvic stability and decreased pain, but there are minority disputes, requiring more in-depth research about the topic.
Keywords: Low Back Pain; Disability; Pilates .